Meroe, Sudan. Archaeological Investigation, Conservation and Site Management at the Meroe Royal Cemeteries/Sudan – The Qatari Mission for the Pyramids of Sudan. The years 2015 and 2016 - Riedel, Alexandra; Wolf, Pawel (e-Forschungsberichte des DAI, 2018)
In 2014, Qatar Museums started the Qatari Mission for the Pyramids of Sudan (QMPS) initiated by HE Sheikh Hassan bin Mohamed bin Ali Al-Thani. The QMPS is Qatar’s archaeological mission in Sudan. It is embedded in the framework of the Qatar-Sudan Archaeological Project (QSAP), a joint initiative of Qatar and the Sudan with the objective of promoting the rich archaeological heritage in the Republic of the Sudan. The mission’s objectives comprise archaeological, architectural and culture-historical research on the pyramid necropolises of the Kingdom of Kush as well as their preservation and presentation in accordance with international guidelines. A holistic approach to the sustainable development of the pyramid sites involves all stakeholder groups, including local communities. To achieve its goals, the QMPS closely cooperates with the National Corporation for Antiquities and Museums (NCAM) in Khartoum and the German Archaeological Institute (DAI) in Berlin. Since 2014 an interdisciplinary team and an international expert network has been established in order to master the complex objectives of QMPS. Work concentrated on the royal pyramid cemeteries of Begrawiya North and South at Meroe, where fieldwork between spring 2015 and spring 2016 has already yielded impressive results.